Este barco é nosso!: do ciberespaço aos caminhos rumo à alteridade - Tonatto, Regiane Cristina (2017)
In times and visions of the world so different from seeing the Other and recognizing it, we seek forms of sociability and paths of interaction and participation of all in a plural space. We live in a context marked by relationships in digital networks, which presents itself as a convergence pole, in which connections produce a force capable of transforming society, people and institutions. The school presents itself as a useful place for various plural possibilities, including by mediated communication through digital media. The research gathers together the voices present in this place and the experiences that surround human convivence side by side with differences. To do this, school tell stories and adventures of people with and without disabilities, that are included in the public school, which is currently based on the inclusive perspective, and thus answers the problem issue that guided it: how otherness is present in an inclusive and conscious cyberspace and what do the Young and adult students with and without disabilities think about the media in relation to accessibility? The theoretical connection of the research mixes the studies of cultural identity and difference through the axiology of Cultural Studies and the study of otherness in Lévinas' philosophy. It assumes the qualitative and interpretative perspective of ethnographic / netnographic basis. First, to understand how speeches and practices on the media and inclusion of people with disabilities operate, the study maps and discusses thirty-seven (37) articles, dissertations, and theses from latin american and caribbean academic production in terms of people with disabilities and education. With this, it decides to think about technologies and their media, not as just a materials acquisition, but also as a possibility to contribute to expand the spaces and times of universality, as well as access and conviviality in the privileged spaces of meetings. Second, it produces a technological artifact from the perspective of the inclusion / exclusion of students with and without disabilities at school, with available access to all in an effort to provide the exchange of cultures. Thus, through the research, a blog called "This boat is ours!" Is created, which considers beyond the principles of universality, the recognition of the Other, in the awareness that it is through the preservation of heterogeneity that it respects the differences and surpasses the idea of the other similar to itself. This dissertation presents reflection issues on the challenges of the school in front of the themes: identity, difference, digital media, inclusion and disability and discusses about the possibilities of digital media in "connecting" paths and forming connection. The blog, thought under the epistemological basis of otherness, was considered by the participants of the research, a way of interaction and participation of all. The result is that the research culminates with the elaboration of a documentary that contemplates the characters of this boat, thus consolidating the paths of alterity in times of necessary universalization.